Moralism in a mad world: Samuel Johnson’s “Business of the biographer” - Jutras, Jessica (My University, 2023)
One of the most prolific authors of the eighteenth century, Samuel Johnson, strives toward intentional moralistic authorship, especially in The Rambler and The Idler periodicals, where he considers such topical studies as biography and conceptions of reality. While exploring Johnson’s publications on moralism, a contradiction between his public statements and personal actions was uncovered. This contradiction begged investigation into the validity and authority of Johnson’s moralism while asking the age-old question of why writers write.
Keywords: Samuel Johnson; moralism